Development of Arduino-Based Flowmeter Sensor Props for Measuring Water Flow in Dynamic Fluid Materials - Rosyida Husniyah; Prabowo Prabowo (IKIP Mataram, 2022)
The purpose of this study is to describe the validity of an Arduino-based flowmeter sensor tool to measure water flow in dynamic fluid materials, as well as the suitability of an Arduino-based flowmeter sensor tool to measure water flow in dynamic fluid materials compared to the theory of continuity principles. Development research using the ADDIE model is the method used (Analysis, Design, Development, Implementation, Evaluation). The validity of the Arduino-based flowmeter sensor is determined by the results of a professional lecturer validator and the accuracy of the test results or the level of accuracy using teaching aids. The accuracy calculation was used to assess the suitability of the Arduino-based flowmeter sensor application for the theory. Based on the data that has been obtained, the validation results, and the accuracy level of the teaching aid have a percentage of 61%, so the validity level of the Arduino-based flowmeter sensor for measuring water flow is included in the very good category. The validation of teaching aids resulted in a percentage of 93.1%, while experimental data using an Arduino-based flowmeter sensor resulted in an average accuracy rate of 99.19%. Meanwhile, the accuracy of teaching aids to the concept of continuity principle was obtained with an average accuracy rating of 98.12%. By holding this practicum activity, students can better understand the concept and improve students' critical thinking. Given that during practical activities, students are required to solve a problem . The accuracy of teaching aids is included in the very good category on the interpretation scale.